ICE manual of health and safety in construction - McAleenan, Ciaran; Oloke, David (ICE manuals., 2010)
Written and edited by experienced construction industry professionals, the 'ICE Manual of Health and Safety in Construction' provides invaluable practical guidance on how hazards can be removed, controlled or managed, through all the stages of construction projects.